2011
DOI: 10.1001/jama.2011.679
|View full text |Cite
|
Sign up to set email alerts
|

Oral vs Intratympanic Corticosteroid Therapy for Idiopathic Sudden Sensorineural Hearing Loss

Abstract: clinicaltrials.gov Identifier: NCT00097448.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
312
3
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(342 citation statements)
references
References 35 publications
10
312
3
17
Order By: Relevance
“…If the 10 patients within 2 weeks from the onset were excluded to eliminate the effect from nature spontaneous recovery, 43.5% patients (27/62) showed clear or partial improvement. These results were similar to or higher than average recovery rate of other studies especially considering the time interval from onset of ISSHL to start treatment ( Xenellis J et al, 2006;Haynes DS et al, 2007;Raymundo IT et al, 2010;Wu HP et al, 2011;Rauch SD et al, 2011;Park MK et al, 2011).…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognosupporting
confidence: 88%
See 1 more Smart Citation
“…If the 10 patients within 2 weeks from the onset were excluded to eliminate the effect from nature spontaneous recovery, 43.5% patients (27/62) showed clear or partial improvement. These results were similar to or higher than average recovery rate of other studies especially considering the time interval from onset of ISSHL to start treatment ( Xenellis J et al, 2006;Haynes DS et al, 2007;Raymundo IT et al, 2010;Wu HP et al, 2011;Rauch SD et al, 2011;Park MK et al, 2011).…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognosupporting
confidence: 88%
“…We decided the criterion valuation basis for effectiveness at least 10 dB decrease in PTA of contiguous 4 frequencies (250, 500, 1000, 2000 Hz) because most of patients visited our clinic after they failed to conventional therapies, so we considered that 10 dB was reasonable comparing other studies (Xenellis J et al, 2006;Rauch SD et al, 2011;Wu HP et al, 2011) After completing the AT, 50% patients (36/72) showed clear or partial improvement. If the 10 patients within 2 weeks from the onset were excluded to eliminate the effect from nature spontaneous recovery, 43.5% patients (27/62) showed clear or partial improvement.…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognomentioning
confidence: 99%
“…A randomized, large-scale, multicenter study demonstrated that intratympanic corticosteroids have the same efficacy as oral steroids for the treatment of sudden SNHL [29] . Although many studies have not shown a positive effect of intratympanic steroid on tinnitus, we demonstrated the therapeutic effects of ITD limited to the acute tinnitus cases in a recent double-blind, randomized, and controlled trial [18] .…”
Section: Discussionmentioning
confidence: 99%
“…For patients who present with symptoms of acute vertigo with or without sudden sensorineural hearing loss, the optimal treatment will be a short course of high-dose steroids, regardless of the imaging findings. 20,21 In the setting of suspected sarcoidosis or primary malignancy, a contrast-enhanced examination is warranted rather than a screening examination. Furthermore, sarcoidosis or leptomeningeal metastases rarely present as isolated sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%